Kolaborasi Guru, Orang Tua Dan Masyarakat Sekolah Dalam Pembentukan Karakter Siswa Melalui Pendidikan Agama Islam - Munawaroh, Lailatul (Prodi PGMI Institut Agama Islam Bani Fattah Jombang, 2025)
ABSTRACT The difficulty of developing religious character in students in this modern era has become the main goal of previous researchers to explain the important role of religious teachers, what strategies should be used, and the benefits of teacher, parent and school community contributions in the process of forming students' religious character. The purpose of this study is to identify the role of Islamic Religious Education teachers, strategies carried out by teachers and collaboration between teachers, parents and the school community in forming good character in students. The type of method used is a Systematic literature review (SLR). This study utilizes Garba Rujukan Digital (Garuda), a repository of Indonesian scientific articles, as a data source. In this study, the author analyzed 5 articles that met the criteria, namely written in Indonesian and published in the 2014-2024 period. The article search was carried out using three main keywords: